Attribution Analysis of Runoff Change in the Upper Reaches of the Liuchong River Basin Based on Coupled Water-energy Balance Equation - LONG Da; DONG Qianjin; YANG Rongfang (Renmin Zhujiang)
Taking the upper reaches of the Liuchong River in Guizhou Province as the study area,this paper first analyzes the trend and abrupt change of the annual runoff at Qixingguan Station in the Liuchong River by the Mann-Kendall test and Pettitt test to find the abrupt change points,then,discusses the reasons of runoff change before and after the abrupt change points by the coupled water-energy balance equation,finally,calculates the contribution rates of precipitation,potential evapotranspiration and underlying surface to runoff change through the sensitivity analysis of their elastic coefficients.The results show that:The depth of runoff in the upper reaches of the Liuchong River shows a significant downward trend from 1971 to 2009,and a significant abrupt change occurred in 1986.By comparing the sensitivity of precipitation,potential evapotranspiration,and underlying surface to runoff change,it is found that the elastic coefficient of precipitation is the highest,followed by the underlying surface index,and finally the potential evapotranspiration,indicating that runoff is the most sensitive to the change of precipitation.In addition,based on the results of the contribution rate of the three factors to the reduction of runoff,it is found that the contribution rate of decreasing precipitation to runoff reduction is as high as 113.3%,followed by the change of underlying surface,with a contribution rate of 14.4% and finally the increasing potential evapotranspiration,with a contribution rate of -27.7%.